Mixed-species malaria infections in humans. - Mayxay, M; Pukrittayakamee, S; Newton, P; White, N (2004)
Mixed-species malaria infections are often not recognized or underestimated. In Asia, surveys usually report that <2% of infections are mixed, whereas therapeutic studies in vivax or falciparum malaria have demonstrated a high prevalence (up to 30%) of infection with the other malaria species during convalescence, suggesting covert co-infection. In epidemiological studies, a high prevalence of cryptic mixed-malaria species infection has been detected by sensitive PCR techniques. Concurrently infecting malaria species are mutually suppressive with Plasmodium falciparum tending to dominate Plasmodium vivax, but P. vivax attenuating the severity of P. falciparum. There is evidence for some cross-species immunity. These interactions have important clinical and public health implications.